Is "friction" responsible for the reduction of fusion rates far below the Coulomb barrier? - Karataglidis, S.; Amos, K.; Giraud, B. G.; Robson, B. A. (HNPS Advances in Nuclear Physics, 2020)
Observed rates of the fusion of interacting heavy ions well below the Coulomb barrier are considerably lower than estimates obtained from penetration factors. An interpretation of this discrepancy has been in terms of tunnelling in semiclassical models, with the observed depletion being taken as evidence of a "friction" under the barrier. An extension of that approach is to consider tunnellin in fully quantal models. We consider tunnelling in one-dimensional models to investigate possible sources for such a friction. Under certain conditions, we find that tunnelling may be enhanced or diminished by up to 50%, which finds analogy with observation, without the invocation of a friction under the barrier.